2019
DOI: 10.1002/jcp.28999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TAF1, SAT1, and ARHGEF9 as DNA methylation biomarkers for hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a major cause of cancer-related deaths worldwide.More than 90% of primary HCC is HCC. Hepatitis C virus (HCV) infection and alcohol consumption have been widely accepted as two major risk factors for developing HCC. Herein, we aimed to identify DNA methylation genes related to both HCV infection and alcohol consumption. In this study, we identified methylation genes that were associated with the risk of HCV infection and alcohol consumption, respectively, by a large-scale bioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In this study, we first reported the correlation between SDHA mutation and tumor stage, indicating its potential predictive value. Although the correlation between TAF1 , BRIP1 , and CBFB mutations and prognosis has been reported, only have been reported in lung cancer 56 58 . Our results suggest that these genes may be related to prognosis in Chinese lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we first reported the correlation between SDHA mutation and tumor stage, indicating its potential predictive value. Although the correlation between TAF1 , BRIP1 , and CBFB mutations and prognosis has been reported, only have been reported in lung cancer 56 58 . Our results suggest that these genes may be related to prognosis in Chinese lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that genetic variation and epigenetic modification can affect the progression of tumors (31). However, the current studies on epigenetic mechanisms mainly focus on DNA methylation and histone modification, which have been found to affect the occurrence, progression and prognosis of HCC (32)(33)(34)(35)(36)(37). m6A methylation is a newly discovered method of RNA chemical modification, and its role in HCC will be gradually revealed.…”
Section: Discussionmentioning
confidence: 99%
“…A number of research studies have unveiled that aberrant DNA Abbreviations 5-aza-dC, 5-aza-2ʹ-deoxycytidine; CGI, CpG island; DEmRNA, differentially expressed mRNA; FC, fold change; HCC, hepatocellular carcinoma; MSP, methylation-specific PCR; MTT, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide; NC, negative control; PZP, pregnancy zone protein; SD, standard deviation; TCGA-LIHC, The Cancer Genome Atlas Liver Hepatocellular Carcinoma. methylation is able to facilitate tumor cell proliferation, invasion and migration of colorectal cancer [8], gastric cancer [9], liver cancer [10,11], HCC [12] and so on.…”
mentioning
confidence: 99%
“…Aberrant CGI methylation of the gene promoter region can activate proto‐oncogenes or silence tumor suppressor genes, leading to altered expression of downstream key genes and consequently promoting the aberrant proliferation of cancer cells [6]. A number of research studies have unveiled that aberrant DNA methylation is able to facilitate tumor cell proliferation, invasion and migration of colorectal cancer [8], gastric cancer [9], liver cancer [10,11], HCC [12] and so on.…”
mentioning
confidence: 99%